The Relationship Between Religiosity and Student Learning Achievement in Fiqh Subjects at State Islamic Junior High School 4, Kuantan Singingi Regency - Makmuri, Muhammad; Murniati, Andi; Afriza, Afriza (Ahlussunnah: Journal of Islamic Education, 2025)
Education is a crucial aspect of human resource development, especially in today's digital age. Student success can be measured by their academic achievement. Through student learning achievement, teachers can help students improve their understanding of fiqh learning. This article discusses the relationship between religiosity and student learning achievement in fiqh subjects at MTs Negeri 4 Kuantan Singingi Regency. This study uses a quantitative approach with a correlation method. The population in this study was all 253 students of MTs Negeri 4 Kuantan Singingi, with a random sample of 155. The instruments used were questionnaires and tests to measure religiosity and documentation of fiqh subject scores. The data analysis technique used questionnaire instrument prerequisite tests: validity and reliability tests. Research prerequisite tests: normality, linearity, multicollinearity, and heteroscedasticity tests. Research hypothesis testing: simple linear regression tests. The results of the data analysis show: There is a significant positive relationship between religiosity and learning achievement in fiqh subjects. One of the keys to educational success in educational output is that students succeed in improving their learning achievement. Student learning achievement can improve through a long process and is influenced by various factors. This study has successfully demonstrated that student religiosity has a significant and strong positive relationship with improving student achievement. This means that student religiosity should be consistently cultivated so that it becomes firmly embedded within students, leading to continued improvement in student achievement. This can lead to student success in their education and all aspects of life.